Penerapan Sistem Cerdas dan Sistem Informasi Geografis pada Aplikasi Layanan Jaminan Bongkar Reklame - Aprisandi, Lalu Wirman; Azwar, Muhamad; Sujaka, Tomi Tri (CORISINDO 2025, 2025)
This study aims to design and develop a web-based billboard permit application system that integrates intelligent system technology and Geographic Information Systems (GIS). The system utilizes the Forward Chaining and Certainty Factor algorithms to provide recommendations on the suitability of billboard placement zones based on expert-defined rules, while Google Maps is used for interactive visualization of billboard locations. Alpha testing results indicate that all system features—ranging from application submission and processing to reporting—function as intended according to the initial design. Meanwhile, beta testing shows a user satisfaction rate of 86.33%, indicating that the system is considered user-friendly, functional, and suitable for implementation within regulatory agencies. In addition to supporting the digitization of public services, the system also enhances the efficiency of monitoring and decision-making regarding non-compliant or expired billboards. This study contributes to the application of information technology to accelerate, simplify, and improve the effectiveness of public services related to billboard permitting.